The preoperative prognostic nutritional index in patients undergoing major gynecologic oncology surgery and its association with postoperative outcomes - Helena Fabiani; Wiji Lestari; Gatot Purwoto (World Nutrition Journal, 2026)
Background: Patients undergoing major surgery for gynecologic cancer often experience postoperative complications. Postoperative complications are influenced by various factors, one of which is nutritional status. The preoperative prognostic nutritional index (PNI), calculated from serum albumin levels and lymphocyte count, is used as a preoperative nutritional parameter and has been associated with postoperative outcomes. Objective: To investigate the association between preoperative PNI and postoperative outcomes in patients undergoing major gynecologic oncology surgery. Methods: This prospective observational study was conducted at Dr. Cipto Mangunkusumo National General Hospital in August-December 2024. Subjects were gynecologic cancer patients aged 18-65 years who underwent major surgery. PNI was calculated based on preoperative serum albumin levels and lymphocyte count. Postoperative complications were assessed within 30 days following surgery using the Clavien-Dindo classification. Statistical analysis was performed using Chi-square or Fisher’s exact test, followed by multivariable logistic regression. Results: A total of 56 subjects were included, with a mean age of 47.8 ± 12.3 years and a median PNI of 50.2 (28.9-61.3). Postoperative complications occurred in 35.7% of subjects, with surgical site infections being the most common. The median PNI was lower in the complication group, although the difference was not statistically significant. In multivariable analysis, advanced tumor stage was the only independent predictor of postoperative complications (odd ratio [OR] 4.74, 95% CI 1.26–17.83, p = 0.021). Low PNI showed a nonsignificant trend toward higher odds of complications (OR 1.71, 95% CI 0.47–6.28, p=0.420). Conclusion: PNI was not statistically significant but showed a trend toward association with postoperative complications, suggesting its potential importance of preoperative nutritional status. Advanced tumor stage was an independent predictor of complications. Further multicenter studies are needed to confirm the prognostic role of PNI in gynecologic oncology surgery.